2022
DOI: 10.1126/sciadv.abj1927
|View full text |Cite
|
Sign up to set email alerts
|

Fish crimes in the global oceans

Abstract: This study provides a global assessment of the linkages between observed fisheries-related offenses across the world’s oceans between 2000 and 2020. We analyze data from the largest existing repository with 6853 events reporting offenses across 18 fishing-related categories, including illegal fishing, human rights abuses, and smuggling. We find that at least 33% of all recorded offenses are associated with 450 industrial vessels and 20 companies originating from China, the EU, and tax haven jurisdictions. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…This major contribution to livelihoods and food security is threatened by unsustainable and often illegal fishing (Doumbouya et al, 2017;Merem et al, 2019;, which itself is often tied to other types of criminal activities (UNODC, 2011;Belhabib and Le Billon, 2022). Illegal fishing in West Africa results in a loss to coastal states of US$2.3 billion annually, benefiting more developed nations and their DWF fleets (Doumbouya et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…This major contribution to livelihoods and food security is threatened by unsustainable and often illegal fishing (Doumbouya et al, 2017;Merem et al, 2019;, which itself is often tied to other types of criminal activities (UNODC, 2011;Belhabib and Le Billon, 2022). Illegal fishing in West Africa results in a loss to coastal states of US$2.3 billion annually, benefiting more developed nations and their DWF fleets (Doumbouya et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…In order to analyze possible links between adjacency and illegal fishing, we compared the official lists of registered and licensed fishing vessels (including "domesticated" or "reflagged" with the host jurisdiction) 6 obtained from the governments for the study sample (Table 1) to the data extracted from the Criminal Record of Fishing Vessels (CRFV © Belhabib, 2018) for the region. The CRFV compiles information on vessels and fishing company infractions from media reports, government reports, automatic identification system (AIS) track analysis, and testimonies from witnesses and informants (Belhabib and Le Billon, 2022). Data are gathered on a daily basis since 2016, whenever these reports are made available.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have reported problems related to climate change, the exploitation of natural resources, and the release of pollutants into the ocean (e.g. Doney et al, 2012;Kühn et al, 2020;Hatje et al, 2021;Belhabib and Le Billon, 2022;Nunes et al, 2022), reinforcing the importance of detecting and monitoring their potential effects on marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%